Rare sulfides enriched in K, Tl and Pb from the Noril'sk and Salmagorsky complexes, Russia: new data and implications. (2nd January 2018) - Barkov, Andrei Y.; Martin, Robert F.; Cabri, Louis J.
Abstract: New results (compositional data and reflectance values) are reported for some rare sulfides enriched in K, Tl and Pb, which are related to djerfisherite, thalfenisite, bartonite, a "Cl-bearing bartonite", or chlorbartonite, and also for shadlunite, from the Noril'sk and Salmagorsky complexes, Russia. Our observations and comparisons with relevant data in the literature imply that: (1) bartonite is probably a S-dominant (or Cl-free) analogue of djerfisherite; and a "Cl-bearing bartonite" and chlorbartonite are probably compositional variants of the djerfisherite–bartonite series. (2) The most probable formulae of bartonite and djerfisherite are (K, Me 2+ )6 (Fe, Cu, Ni)25– x S26 (S, Cl) and (K, Me 2+ )6 (Fe, Cu, Ni)25– x S26 (Cl, S), where 0 ≤ x ≤ 5, respectively. (3) Two independent substitution mechanisms probably operate in the natural series. A coupled substitution [ Me 2+ + S 2– ↔ K + + Cl – ] is reflected by an observed deficit in K, accompanied by the incorporation of Me 2+ (Pb, Fe, or Ni) in the K site. Another mechanism is inferred to be [2Fe 3+ + 〈 ↔ 3Fe 2+ ], which assumes the existence of vacancy-type defects at the Me site. Thus, the second mechanism could possibly control the existing variations of Σ(Fe, Cu, Ni) in the range of ∼21 to 25 a.p.f.u., documented in djerfisherite- and bartonite-type minerals. The minerals analysed from Noril'sk, which are free of Cl and related to bartonite and to a Tl-dominant analogue of bartonite (unnamed species), probably crystallized from microvolumes of late fluid rich in K and Tl, under conditions of relatively low oxygen fugacity in the environment. Uniform contentss of Fe and Cu, observed in coexisting phases of normal (Cl-bearing) djerfisherite and bartonite (or Cl-free analogue of djerfisherite) at Salmagorsky imply that they reached equilibrium with regard to the distribution of these elements during crystallization. These phases probably formed as a result of fluctuations in the ratios of sulfur and chlorine fugacity in a fluid at a postmagmatic hydrothermal stage.